Semi-Automatic System For The Extraction Of Anatomical Objects From Abdominal MRI Images - Zaman Sarker, Md. Shakowat (2007)
The main goal of this research is to design a system for automatic extraction of anatomical objects from MRI images of the abdomen, using morphological techniques as the key tool. The system consists of two major parts: image segmentation and object extraction.